2003
DOI: 10.1046/j.1365-313x.2003.01679.x
|View full text |Cite
|
Sign up to set email alerts
|

CYP79F1 and CYP79F2 have distinct functions in the biosynthesis of aliphatic glucosinolates in Arabidopsis

Abstract: SummaryCytochromes P450 of the CYP79 family catalyze the conversion of amino acids to oximes in the biosynthesis of glucosinolates, a group of natural plant products known to be involved in plant defense and as a source of flavor compounds, cancer-preventing agents and bioherbicides. We report a detailed biochemical analysis of the substrate specificity and kinetics of CYP79F1 and CYP79F2, two cytochromes P450 involved in the biosynthesis of aliphatic glucosinolates in Arabidopsis thaliana. Using recombinant C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
196
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(222 citation statements)
references
References 42 publications
16
196
0
Order By: Relevance
“…These mutants exhibit massive proliferation of shoots, together with other developmental defects. The quantification of hormone levels in sps/cyp79F1 mutant plants indicates that both auxin and cytokinins are higher in the mutants, but the phenotypes of the sps/cyp79F1 plants are consistent with higher levels of cytokinins rather than auxins as the key factor responsible for the change in branching pattern (Tantikanjana et al, 2001).Despite the fact that sps/cyp79F1 plants resemble hormone mutants, biochemical studies have shown that SPS/CYP79F1 gene encodes an enzyme catalyzing metabolism of both short-chain and long-chain elongated Met-derivatives in the biosynthesis of aliphatic glucosinolates (Hansen et al, 2001;Chen et al, 2003). Glucosinolates are a group of secondary plant metabolites known to play a role in plant defense and are sources of flavor compounds, cancer-preventing agents, and bioherbicides.…”
mentioning
confidence: 88%
“…These mutants exhibit massive proliferation of shoots, together with other developmental defects. The quantification of hormone levels in sps/cyp79F1 mutant plants indicates that both auxin and cytokinins are higher in the mutants, but the phenotypes of the sps/cyp79F1 plants are consistent with higher levels of cytokinins rather than auxins as the key factor responsible for the change in branching pattern (Tantikanjana et al, 2001).Despite the fact that sps/cyp79F1 plants resemble hormone mutants, biochemical studies have shown that SPS/CYP79F1 gene encodes an enzyme catalyzing metabolism of both short-chain and long-chain elongated Met-derivatives in the biosynthesis of aliphatic glucosinolates (Hansen et al, 2001;Chen et al, 2003). Glucosinolates are a group of secondary plant metabolites known to play a role in plant defense and are sources of flavor compounds, cancer-preventing agents, and bioherbicides.…”
mentioning
confidence: 88%
“…3), through the activity of gene products of the CYP79 gene family, each of which has substrate specificity for different amino acid precursors. For example, within Arabidopsis, the products of CYP79F1 and F2 catalyse the conversion of elongated homologues of methionine to the corresponding aldoximes [45], CYP79B2 and CYP79B3 convert tryptophan to their aldoximes [46] and CYP79A2 convert phenylalanine to its aldoxime [47]. The aldoxime conjugates with cysteine which acts as the sulphur donor, and then cleaved by a C -S lyase [48].…”
Section: Molecular Genetics and Biochemistry Of Glsmentioning
confidence: 99%
“…Table 1 shows the kinetic parameters and the initial (fixed) concentration of MTOB used in the rate laws. Kinetic values set in Roman type were obtained from Textor et al (2004Textor et al ( , 2007, or, in the case of the CYP79F1/F2 enzymes, from Chen et al (2003). Values set in italics were derived from assumptions given above or chosen from preliminary simulations to optimize correspondence of the model with actual glucosinolate chain-length distributions observed.…”
Section: Rate Laws and Kinetic Parametersmentioning
confidence: 99%
“…k = 7 * 10 -7 a Parameters given in roman are experimental kinetic data, while those written in italics have been optimized to fit the model. Experimental data for MAM3 was obtained in Textor et al (2007); for MAM1 in Textor et al (2004) and for Cyp79F1 and F2 in Chen et al (2003). Constant concentration of the external metabolite OMTB = 1 lM transamination reactions (which are not yet characterized) by unknown parameters, increasing computational difficulties.…”
Section: ) Amentioning
confidence: 99%